2011
DOI: 10.1158/1535-7163.mct-10-0693
|View full text |Cite
|
Sign up to set email alerts
|

Connexin-26 Is a Key Factor Mediating Gemcitabine Bystander Effect

Abstract: Gemcitabine is a nucleoside analogue with anticancer activity. Inside the cell, it is sequentially phosphorylated to generate the active drug. Phosphorylated nucleoside analogues have been shown to traffic through gap junctions. We investigated the participation of gap junctional intercellular communication (GJIC) as a possible mechanism spreading gemcitabine cytotoxicity in pancreatic tumors. Immunohistochemical analysis of pancreatic cancer biopsies revealed increased connexin 26 (Cx26) content but loss of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…It may be that the changes we see in Cx43 expression over time are associated with specific lesions or stages of PDA; to examine this idea a rigorous histological analysis of Cx43 localization is presently underway. Previous studies have indicated that Cx26 is overexpressed in human pancreatic cancer (Garcia-Rodriguez et al 2011; Kyo et al 2008). It will be interesting to confirm that this occurs in the mouse model and to compare the Cx26 expression profile to what we see with Cx43.…”
Section: Discussionmentioning
confidence: 97%
“…It may be that the changes we see in Cx43 expression over time are associated with specific lesions or stages of PDA; to examine this idea a rigorous histological analysis of Cx43 localization is presently underway. Previous studies have indicated that Cx26 is overexpressed in human pancreatic cancer (Garcia-Rodriguez et al 2011; Kyo et al 2008). It will be interesting to confirm that this occurs in the mouse model and to compare the Cx26 expression profile to what we see with Cx43.…”
Section: Discussionmentioning
confidence: 97%
“…GJIC can increase the susceptibility of cancer cells to cytotoxic agents through connexin-mediated "bystander effects" in pancreatic cancer (56). BxPC3 cells in which GJIC is artificially increased exhibit bystander cytotoxicity when exposed to gemcitabine (56 -58).…”
Section: Discussionmentioning
confidence: 99%
“…Transfection or transduction of Cx26 and Cx43 results in increased GJIC, and consequently leads to an increased bystander effect seen in suicide gene therapy [7], [19]. Alternatively, a number of classes of chemicals, including gemcitabine [20], cAMP [21], and retinoids [22], have been reported to increase Cx26 and Cx43 and, subsequently, GJIC.…”
Section: Introductionmentioning
confidence: 99%